ECONOMIC DEVELOPMENT POLICY TOWARDS THE DEVELOPMENT OF MSMEs - Raihanah Daulay; Isnaini Harahap; Zuhrinal Nawawi (RADJA PUBLIKA, 2024)
Indonesia's development aims to improve the ability and competitiveness of the Indonesian people in order to be able to reduce poverty and achieve the welfare mandated at the opening of the UUD1945. The purpose of this study is to determine the development carried out by empowering and developing micro, small and medium enterprises through the establishment of various policies and empowering MSMEs through regulations that encourage and develop MSMEs. The results of Government research through policies have been able to improve the performance of MSMEs. The performance shown by micro enterprises as the foundation of the National Economy is able to absorb 96% of the workforce which plays an important role in the global economy. Improve community welfare and contribute to economic development with an increase in GDP by 60.5%, business units by 99%. MSMEs are a booster of economic recovery during crises, including the Covid19 pandemic.